Pengaruh Kecepatan Publikasi Berita terhadap Persepsi Akurasi Informasi yang Dikonsumsi Masyarakat Umum pada Akun Instagram Bengkulu Info - Fidya Adesya; Delfan Eko Putra (Lembaga Yasin AlSys, 2026)
The development of Instagram as a medium for disseminating local information encourages the public to obtain news quickly, including through the Bengkulu Info account. However, the speed of news publication is not always accompanied by an equally strong public perception of information accuracy. This study aims to analyze the influence of news publication speed on the perceived accuracy of information consumed by the general public on the Bengkulu Info Instagram account. This study employed a quantitative approach with an explanatory survey design. The research sample consisted of 15 respondents selected through purposive sampling based on the criterion of having followed or consumed information from the Bengkulu Info Instagram account. Data were collected using a Likert-scale questionnaire and were then analyzed through descriptive statistics, reliability testing, normality testing, correlation, simple linear regression, and the coefficient of determination. The results showed that news publication speed had a positive relationship with perceived information accuracy, with a correlation value of 0.496 and an R Square value of 0.246. However, the significance value of 0.060 indicates that this influence was not yet significant at the 0.05 level. These findings affirm that news publication speed plays a role in shaping audience perceptions, but information accuracy remains influenced by source credibility, clarity of information, and audience experience. The conclusion of this study emphasizes the importance of balancing publication speed and information accuracy in the management of local news-based social media. The implications of this study provide a contribution to digital communication studies and practical input for managers of local information accounts in improving the quality, clarity, and credibility of published information.